Iot-Integrated Built-In Doorbell and Monitoring System - Sanmuga Raja, Jeviena Rani; Azizul Azhar Ramli (Applied Information Technology And Computer Science, 2025)
The rapid evolution of security needs has outpaced traditional systems, which often lack real-time notifications, remote accessibility, and integration, creating vulnerabilities that demand smarter, connected solutions. VisionDoor: Built-in Doorbell and Monitoring System leverages IoT technologies to bridge these gaps, offering an efficient and comprehensive smart doorbell solution. This project focuses to desig, developing and testing VisionDoor to enhance security through real-time monitoring, facial recognition, motion detection, and remote access. By prioritizing user-friendliness and cost-effectiveness, it caters small-scale applications and modern security challenges. A Prototyping-Oriented Software Development Life Cycle is chosen to ensure iterative development, enabling continuous refinement through real-world testing. The system is developed using Raspberry Pi, the OpenCV library, and a Flutter-based mobile app with Firebase for real-time data processing. VisionDoor demonstrates improved security management through features like facial recognition, real-time notifications, efficient motion detection, and remote access, offering enhanced user control over premises and reducing response times. By combining advanced features such as automated notifications and real-time monitoring, VisionDoor empowers users to maintain robust security remotely. Its dual modes Sentry and Normal, offer flexibility for continuous monitoring or targeted alerts, meeting the needs of residential and small business users alike. The findings underscore the transformative impact of IoT on security, paving the way for smarter, more connected systems.